PERAN AKUNTANSI MODERN DALAM PEMBANGUNAN EKONOMI INDONESIA - Ahmad Hilmy (Nomico, 2024)
Globalization creates high competitiveness of countries globally. In order to overcome this, it is necessary to have a role for modern accounting in planning and deciding policies for equitable distribution and economic development in Indonesia as a developing country. This research uses a descriptive qualitative research method with secondary data sources originating from literature reviews in the form of books, scientific works and online websites related to research data. Based on the results of research conducted, it shows that Indonesia needs the application of modern accounting to restore and improve the country's economy. Accounting will play a role in controlling costs, operations, reporting and planning so that fraud does not occur in the context of Indonesia's economic development as a developing country. Accounting will also provide the latest data or report information that can be used by the government or interested parties.